Ant colony optimization based energy efficiency for improving opportunistic routing in multimedia wireless mesh network - S. Harikishore; V. Sumalatha (Institute of Advanced Engineering and Science, 2019)
Opportunistic Routing (OR) is developing as a favourable prototype to diminish performance deprivation in Wireless Mesh Networks (WMNs) owing to changing channel conditions and link breakages. When a flow of data is forwarded towards their destination, intermediate forwarders can attune the information of the route carried by the nodes. However, OR does not solve these problems such as routing efficiency and Energy Consumption. If the necessary energy is not presented, the packet is rejected and the delay occurs in the network. To overcome these problems, an Ant Colony Optimization based Energy Efficiency for improving opportunistic routing in Multimedia WMN (ACO-EE) is proposed. In this scheme, we develop the optimal energy strategy based on optimal transmission distance and remaining energy computation is saving node energy and enhancing the network lifetime. The ant colony optimization based route formation is to improve both the energy efficiency and opportunistic routing efficiency in WMN.Simulation results show that ACE-EE can effectively reduce the energy utilization of nodes and extend the network lifetime.